Longitudinal effects of syndemics on HIV-positive sexual minority men’s sexual health behaviors - Harkness, Audrey (Arch Sex Behav, 2019)
OBJECTIVE: This study examined the longitudinal effects of co-occurring psychosocial concerns, or syndemics, on HIV-positive sexual minority men’s likelihood of engaging in serodiscordant condomless anal sex (CAS), a health behavior with implications for personal and public health. METHODS: Participants included 390 HIV-positive sexual minority men from two prior secondary prevention trials. Over the course of the one-year data collection period (up to 5 observations per participant), participants completed self-report measures of CAS, as well as six syndemic factors: post-traumatic stress disorder, childhood sexual abuse, depression, anxiety, alcohol abuse, and poly sub stance/stimulant use. We employed multilevel modeling to examine the longitudinal additive effect of syndemics on serodiscordant CAS (binary) over the one-year period. RESULTS: The number of syndemic conditions was a significant predictor of CAS, with each additional syndemic associated with 1.41 greater odds of CAS (p = 0.0004; 95% CI [1.16, 1.70]). Both the between- (p = 0.0121, 95% CI [1.07, 1.69]) and within-person (p = 0.01, 95% CI [1.11, 2.10]) effects of syndemics were significant predictors, showing that an increase in the number of syndemic conditions across person and time both increased odds of CAS. CONCLUSIONS: Interventions addressing HIV-positive sexual minority men’s sexual health behaviors should address the potential impact of co-occurring psychosocial concerns that affect these behaviors. This will benefit this population’s personal sexual health and reduce transmission of HIV and STIs among sexual minority men.